The Impact of Climate Change on Economic Growth and Development in Sub-Saharan Africa - Mendong, Muh. Mu'min (Professorline, 2024)
Climate change harms economic sectors in sub-Saharan Africa, especially agriculture, tourism, forestry, and the energy sector. By 2050, climate change could cost more than 3 percent of GDP and threaten more than 100 million people in Africa with food insecurity, poverty, and displacement. Several African countries, such as Ethiopia, have agreed on several action plans to strengthen measures to combat climate change, such as developing light industry, aviation, and infrastructure. This study aims to analyze how climate change affects productivity and economic growth in sub-Saharan Africa and make policy recommendations to reduce these adverse effects.